2022
DOI: 10.1038/s41467-022-31247-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 intra-host recombination during superinfection with Alpha and Epsilon variants in New York City

Abstract: Recombination is an evolutionary process by which many pathogens generate diversity and acquire novel functions. Although a common occurrence during coronavirus replication, detection of recombination is only feasible when genetically distinct viruses contemporaneously infect the same host. Here, we identify an instance of SARS-CoV-2 superinfection, whereby an individual was infected with two distinct viral variants: Alpha (B.1.1.7) and Epsilon (B.1.429). This superinfection was first noted when an Alpha genom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…First, genetic recombination is the key evolutionary mechanism that is continuously reshaping SARS-CoV-2 genetic diversity 48 . Second, recombination is a widespread phenomenon in SARS-CoV-2 and therefore, although some of the previously detected SARS-CoV-2 recombinant lineages have shown limited circulation at a population level, it remains possible that highly-transmissible and/or pathogenic recombinant lineages emerge in the future 49 . This underlines the need for continuous efforts to maintain an effective genomic surveillance of emerging recombinants to limit their spread.…”
Section: Recombination In Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…First, genetic recombination is the key evolutionary mechanism that is continuously reshaping SARS-CoV-2 genetic diversity 48 . Second, recombination is a widespread phenomenon in SARS-CoV-2 and therefore, although some of the previously detected SARS-CoV-2 recombinant lineages have shown limited circulation at a population level, it remains possible that highly-transmissible and/or pathogenic recombinant lineages emerge in the future 49 . This underlines the need for continuous efforts to maintain an effective genomic surveillance of emerging recombinants to limit their spread.…”
Section: Recombination In Sars-cov-2mentioning
confidence: 99%
“…With the progression of COVID-19 pandemic and evolution of genetically divergent SARS-CoV-2 lineages/sublineages, viral recombinants harbouring mutations acquired from distinct lineages or sublineages to reshape SARS-CoV-2 genetic diversity that confer pathogenic properties distinct from the parental lineage, are becoming a major challenge [8][9][10][11][12][13][14][15][16][17][18]. Vaninsberghe et al [13] identified 1,175 putative recombinants within the first year of SARS-CoV-2 circulation after analysing the 537,360 complete SARS-CoV-2 genome sequences available on Global Initiative on Sharing All Influenza Data (GISAID).…”
Section: Recombination In Sars-cov-2mentioning
confidence: 99%
“…Another mechanism that has been proposed to drive SARS-CoV-2 variants' emergence is recombination [23][24][25][26]. For positive sense-RNA viruses, recombination can occur within a cell that was coinfected with more than one genomic species via a process known as 'strand switching' mediated by the viral RdRp, producing chimeric subgenomic RNA and proteins [27,28].…”
Section: Understanding Sars-cov-2 Long Game: Mechanisms For Viral Evo...mentioning
confidence: 99%
“…Along with the predominant circulation of the Omicron variants, several recombinant variants of SARS-CoV-2 have emerged ( He et al., 2022 ; UK Health Security Agency, 2022 ; Wertheim et al., 2022 ). Among the Omicron-recombinant variants ( UK Health Security Agency, 2022 ), the XD variant is from recombination of the Delta variant and the Omicron BA.1 subvariant at the site nt 21643 (numbered as the prototype strain NC_045512.2, the same hereafter) and the site nt 25581; the XE variant is a recombinant variant between the Omicron BA.1 and BA.2 subvariants at the site nt 11537; the XF variant is a recombinant between the Delta variant and the Omicron BA.1 subvariant at the site nt 5386.…”
Section: Introductionmentioning
confidence: 99%
“…Among the Omicron-recombinant variants ( UK Health Security Agency, 2022 ), the XD variant is from recombination of the Delta variant and the Omicron BA.1 subvariant at the site nt 21643 (numbered as the prototype strain NC_045512.2, the same hereafter) and the site nt 25581; the XE variant is a recombinant variant between the Omicron BA.1 and BA.2 subvariants at the site nt 11537; the XF variant is a recombinant between the Delta variant and the Omicron BA.1 subvariant at the site nt 5386. Besides the Omicron-recombinant variants, Alpha-Epsilon ( Wertheim et al., 2022 ) and Beta-Delta ( He et al., 2022 ) recombinant variants were also reported. Although the pathogenicity and transmissibility of the SARS-CoV-2 recombinant subvariants remain largely undetermined and required further evaluation, previous reports have suggested elevated transmissibility and enhanced pathogenicity of the recombinant coronaviruses ( Phillips et al., 1999 ; Su et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%